The New Economic Geography of the Northern Greek Border Regions - Lefteris Topaloglou; George Petrakos (European Regional Science Association (ERSA), 2006)
The European Union's eastward enlargement following 1st May 2004, has brought in the foreground a new geography in Europe, changing the EU's external borders. The re-allocation of activities, opportunities and threats are changing the role and significance of the borders. Within this context borders and border regions have become an issue of great importance during the last fifteen years in both the areas of scientific research and policy making. The overall picture of the new dynamics occurring at the external EU border regions, in particular, remains rather unclear. The issue being dealt in this article focuses on the dominant policies, practices and perceptions in the Northern Greek border regions with Albania, FYROM and Bulgaria. The region of our focus is one of the most economically, socially and politically fragmented space in Europe, that has a low level of interaction and a mosaic of policies and restrictions towards each other. The paper attempts to answer to which degree cross border interaction (CBI), cross border expectations (CBE) and cross border policies (CBC) are associated with geography, urban system, obstacles, images of the "others", real economy and other parameters. The empirical analysis is based on a survey carried out in nine cross border areas in the EU's external borders under the EXLINEA research program. The empirical work involved: a) Standardised questionnaires b) In depth interviews and c) focus group, data and document collection. Triangulation was used in the attempt to verify the validity of the various data sources as well as the methodology chosen.
Keywords: 330